1989
DOI: 10.1017/s0950268800030144
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of drinking water quality in rural Nicaragua

Abstract: SUMMARYOne hundred and fifty-three water samples from rural Nicaragua were examined for the presence of faecal coliforms during both wet and dry periods. A linear model was fitted by analysis of covariance with the logarithm of the faecal coliform count as the dependant variable. As expected, traditional water sources were grossly contaminated at all times whereas piped water sources were much cleaner. Hand-dug protected wells had significantly higher levels of faecal contamination than unprotected riverside w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 14 publications
2
36
0
Order By: Relevance
“…Site I downstream of this river was found to be more contaminated than site II upstream probably due to human and animal faecal contamination. The contamination of natural water sources by faecally derived organisms has been reported elsewhere [6,19,20]. Pipeborne treated water from comparatively older Mambogo distribution system had higher microbial counts than water from a dam on the relatively new Mafiga distribution system.…”
Section: Resultsmentioning
confidence: 79%
“…Site I downstream of this river was found to be more contaminated than site II upstream probably due to human and animal faecal contamination. The contamination of natural water sources by faecally derived organisms has been reported elsewhere [6,19,20]. Pipeborne treated water from comparatively older Mambogo distribution system had higher microbial counts than water from a dam on the relatively new Mafiga distribution system.…”
Section: Resultsmentioning
confidence: 79%
“…Correlation and stepwise multiple regressions were used to examine the relationships between per capita water consumption and eleven potential predictors. The predictors were chosen based on the review of the results of studies conducted by Sandiford et al, (1990); Thompson et al,(2001); Gazzinelli et al, (1998) and House-Peters and Chang, (2011). Collinearity diagnostics suggested that multicollinearity amongst the variables was not a concern.…”
Section: Discussionmentioning
confidence: 99%
“…All other variables were reentered to assess their contributions to the success of the model, and the variables that did not contribute significantly to the model were removed. The stepwise method ensured that only a small possible set of determinants was included in the model, and therefore it also gave the minimum number of variables needed to determine water use (Sandiford et al 1990;Gazzinelli et al 1998). Table 1 indicates the variables and the relationship with per capita water consumption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations